Phytochemical Screening and Biological Activities of Kigelia africana Fruit Extracts - Sagi Sowmika, Vangala Nitish Reddy, Bojjala Sravya, Radha Yadamuri, Muppuru Muni Kesavulu (JOURNAL OF PHARMACEUTICAL ANALYSIS, 2025)
Phytochemicals have a widespread role in traditional medical systems and are essential in the treatment of many illnesses. It is well known that medicinal plants are abundant in bioactive substances with potential for treatment. In this study Kigelia africana (sausage tree) fruits were collected, shade-dried, powdered, and used to extract phytochemicals with water and organic solvents. The Standard phytochemical screening procedures were applied to the extracts in order to detect the presence of secondary metabolites and additional constituents. Numerous secondary metabolites, including flavonoids, alkaloids, tannins, saponins, and phenolic compounds, are found in Kigelia africana, which is well known for its therapeutic benefits. The ethanol extract of fruit revealed the presence of carbohydrates, alkaloids, proteins, flavonoids, tannins, saponins, glycosides, cholesterol, triterpenoids, phytosterols, and phenolic compounds. The antibacterial activity was evaluated using ethanol and acetone as solvents using the Gram-positive bacteria Streptomyces erythraeus and Bacillus subtilis. Both ethanol and acetone extracts had shown good antibacterial properties against the microorganisms. Additionally, tests indicated that the plant exhibits antioxidant and anti-inflammatory activities. These results offer a phytochemical basis for Kigelia africana’s traditional usage in the treatment of infections, inflammation, and oxidative stress diseases. The abundance of different and effective phytochemicals encourages future pharmacological research and the possible creation of plant-based medicinal medicines are supported by the existence of a variety of strong phytochemicals.